Word’s Contextual Predictability and Its Character Frequency Effects in Chinese Reading: Evidence From Eye Movements - Liu, Zhifang; Liu, Xuanwen; Tong, Wen; Fu, Fuyin (Frontiers in Psychology, 2020)
With two eye movements tracking experiments, present study sought to establish whether predictability of target words facilitate characters processing in Chinese reading. Target Words embedded in sentences in both experiments were composed by 2 Chinese characters. Predictability of target words were manipulated in both experiments, beyond that, frequency of targets' first characters were manipulated in Experiment 1, frequency of targets' second characters were manipulated in Experiment 2. Pervasive predictability effects were observed on almost all of eye movement measures in both experiments. It also yield reliable characters frequency effect in Experiment 1 & 2, on some measures. None reliable interaction effects of predictability and first character frequency were observed in Experiment 1, but predictability and second character frequency interactively impacted on some measures of eye movement. Theoretical implications of the data are discussed.